Un modelo hedónico para los alquileres turísticos en la ciudad de Sevilla - Miguel Ángel Solano Sanchez; Julia M. Nú\~nez Tabales; José María Caridad Ocerín (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– The boost of the accommodation type called vacation rentals (tourist apartments and dwellings) experienced worldwide in recent years thanks to the rise of the Internet and P2P networks arouses interest in the analysis of these new stay formulas. The aim of this research is the elaboration of an econometric model through hedonic pricing method (HPM) which establishes the fundamental variables in the determination of the daily rate in vacation rentals. This methodology, has been largely used in real estate valuation and price determination in tourist accommodation (mostly hotels), although scarcely regarding vacation rentals valuation. Through the data collected from Seville -the largest city in southern Spain- an econometric model for valuation of vacation rentals is obtained in which stand out as main explanatory variables the location of the property, size, amenities, as well as the time period which the price is taken. The results of the present study could interest both owners and potential clients of vacation rentals, in order to know if the daily rate is in accordance with what would normally offer the market under those circumstances.
Keywords: C51; C52; 330; vacation rentals; touristic apartments; touristic dwellings; hedonic pricing method; Seville